Sustainable Development Goals (SDGs) and Policy Frameworks for Development in Africa - Dinbabo, Mulugeta F.; Mazani, Perfect (New Agenda: SA Journal of Social and Economic Policy, 2025)
The Sustainable Development Goals (SDGs) are a universal call to action adopted by all UN member states in 2015, aiming to end poverty, protect the planet and ensure prosperity for all by 2030. The SDGs promote inclusive development through sustainable economic growth, social inclusion and environmental protection. Using secondary data analysis, this paper investigates the opportunities and challenges associated with the SDGs, examining how national policies connect with them and evaluating the implementation of relevant treaties and conventions. Key findings highlight institutional capacity gaps, the impact of political will and the importance of international alliances in achieving the SDGs. The study also emphasises the need for effective monitoring and evaluation systems to track success, ensure accountability and promote adaptive policy approaches. These findings contribute to the discourse on sustainable development and offer a roadmap for policy-makers and organisations committed to advancing sustainable development across Africa.